Targeted treatment of vascular anomalies - Ashley T. Ng, BS; Richard L. Tower; Beth A. Drolet (Wolters Kluwer, 2021)
Vascular anomalies comprise an array of congenital developmental disorders that can lead to significant disfigurement and physiologic disarray. The vast multitude of clinical phenotypes has inherently led to misdiagnosis and patients and families enduring long diagnostic odysseys of medical care. Although the observed variation in disease manifestations remains poorly understood, targeted next-generation sequencing has pivoted our understanding of the pathobiology of vascular anomalies and, for the first time, uncovered potential pharmacologic targets for these disorders. In this review article, we highlight current and developing targeted therapies for vascular anomalies, namely phosphoinositide 3-kinase and mitogen-activated protein kinase pathway inhibitors, and discuss the future directions of targeted therapies.